The Impact of Sales Promotion and Electronic Word-of-Mouth on Originote Products via the TikTok Shop Application on Purchasing Decisions in Palembang City - Annisa, Audi Rizky; Putri, Yulia Hamdaini; Mavilinda, Hera Febria (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This study examines the impact of sales promotions and electronic word of mouth (e-WOM) about The Originate items in the TikTok Shop application on purchasing decisions in Palembang. This study aims to elucidate the significance of promotional methods and electronic word-of-mouth in enhancing customer purchasing decisions for companies.Methodology: This research used quantitative methods with data collection techniques through questionnaires involving 100 respondents. The data obtained were analyzed using multiple linear regression analysis to test the influence of each independent variable on the dependent variable.Result: The research shows that sales promotions and electronic word-of-mouth (e-WOM) have a big effect on people's decisions to buy Originote products in the TikTok Shop app at the same time. Sales promotions exert a greater influence on purchasing decisions than electronic word-of-mouth.Conclusions: The study concludes that promotion (X?) and e-WOM (X?) positively influence purchasing decisions for The Originote products on TikTok Shop in Palembang City. The F-test results show that both variables together significantly impact purchasing decisions. In the digital marketing era, a strong promotion strategy combined with positive e-WOM can significantly boost consumer buying interest.Limitations: This research only focuses on users of the TikTok Shop application in Palembang City, so the results cannot be generalized to other regions and only research Sales Promotion and e-WOM. Future research should consider other variables, such as price and product quality, for a more comprehensive analysis.Contribution: This research offers ideas for business professionals, particularly The Originate, to optimize sales promotion methods and leverage e-WOM as an efficient digital marketing instrument. These findings constitute an academic addition to the examination of digital marketing in the e-commerce era.